Déficit de atención e hiperactividad, estrategias para tratamiento en aula en escuela de educación básico particular San Andrés periodo académico 2023-2024 - Manchay Vasquez, Wendy Anthonella (2024)
This curricular integration paper is aimed at analysing Attention Deficit and Hyperactivity Disorder, along with teaching strategies to address attention in the classroom at the private basic primary school "San Andrés" from the city of Loja, school year 2023-2024. It is a significant problem since it greatly affects students in the teaching-learning process, due to the fact that teachers don’t have the necessary knowledge to apply strategies that help these students improve academic difficulties. In this study, in order to analyse the knowledge that teachers have regarding different strategies, we made use of a survey, focusing mostly on the use of different strategies within the classroom to improve students' academic performance. This study showed us, through observation and questions, that students exhibit distraction, little attention, and therefore they do not finish their classwork as they should, consequently affecting their school performance. A data triangulation was executed, which evidenced that teachers lack the necessary knowledge about Attention Deficit and Hyperactivity Disorder, and are unaware of teaching strategies for addressing attention in the classroom for children with attention deficit and hyperactivity.